Statistical analysis of turbulent thermal free convection over a small heat source in a large enclosed cavity. (25th January 2016) - Zhang, Xiwen; Yu, Jiajia; Su, Genghui; Yao, Zhaohui; Hao, Pengfei; He, Feng
Highlights: The detailed statistical analysis of temperature is carried out. Thermal boundary layers and fluctuation features are affected by edge effect. The center region of the cavity is less affected by edge effect. Temperature intermittent is huge where thermal plumes initially form and converge. Abstract: To investigate natural convection in an enclosed cavity, a rectangular experimental cavity is established. Transient temperature along the central line ( l 1 ) and the vertical axis of the longer side ( l 2 ) of the heat source is measured by using a T type thermal couple. Thermal boundary layers are presented. The center and border of the hot plate show different characteristics of thermal boundary layers and fluctuation features. The efficiency of energy transformation from large scales to smaller ones enhances with increased height and reaches an acme at the height of 5–8 mm, the juncture of thermal boundary layers. Flow field could be divided into three regions according to the analysis of power spectrum distribution (PSD). Numerical results show that the unsteady characteristics are extremely distinctive where the two thermal plumes initially form (Z/H = 0.2) and converge (Z/H = 0.55) because of edge effect. Thus, two peaks exist in the skewness and kurtosis of temperature.